Adrenal Insufficiency in Young Children: a Mixed Methods Study of Parents' Experiences. Issue 6 (7th July 2018) - Simpson, Amy; Ross, Richard; Porter, John; Dixon, Simon; Whitaker, Martin J.; Hunter, Amy
Abstract: Research into adrenal insufficiency (AI) and congenital adrenal hyperplasia (CAH) in children has focused largely on clinical consequences for patients; and until recently, the wider experience of the condition from the perspective of other family members has been neglected. In a mixed methods study, we captured the experiences of parents of young children affected by AI/CAH, including their views on the psychosocial impact of living with and managing the condition. Semi‐structured interviews were carried out in the UK and an online survey was developed, translated and disseminated through support groups (UK and the Netherlands) and outpatient endocrinology clinics (Germany). Challenges associated with diagnosis, treatment, support and the future were identified. For UK parents, the diagnosis period was characterised by a lack of awareness amongst healthcare professionals and occurrences of adrenal crisis. Parents reported burden, anxiety and disruption associated with the intensive treatment regimen. Parents adjusted and gained confidence over time yet found delegating responsibility for medication difficult and worried about the future for their child. Access to psychological support and contact with other families was reported as highly beneficial. The findings of the study provide critical context for future studies and for informing how parents and families can be better supported. Prenatal genetic counselling for parents who already have an affected child will include an explanation of recurrence risk but should also focus on providing information and reassurance about diagnostic testing and care for their newborn.